Studies on Potheae (Araceae) of Borneo II: Pedicellarum M.Hotta subsumed into Pothos L., and recognition of three new species - Wong, Sin Yeng; Joling, Jyloerica; Pereira, Joan T.; Damit, Alviana; Boyce, Peter C.; Hay, Alistair (Firenze University Press, 2020)
Pedicellarum is subsumed into Pothos as Pothos paiei. Four species, three taxonomically novel (Pothos degenerans, ecclesiae and P. fractiflexus) and one pre-existing (Pothos oliganthus) are discussed. The reproductive structures are reinterpreted and floral terminology used in this paper is in line with paving the way to interpreting the ‘inflorescence’ of Pothos, and indeed of all other aroids, as a unique array of structures that are neither flowers nor inflorescences as defined by current prevailing orthodoxy, but something of both.